(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The role of phrases in learning Turkish is very important. In addition to learning words separately in the process of learning a language, learning to use them in context, that is, in phrases, helps to understand the true meaning of the language and use it correctly. A phrase is a unit of language formed by the joint use of several words, which means a specific meaning, which is different from the separate meaning of words. That is why phrases play an important role in language learning.